Bioethics: the values of life in the age of advancing biosciences - Hashi, Abdurezak Abdulahi (Darul Tashih, 2021)
This book, Bioethics, the Values of Life in the Age of Advancing Biosciences, addresses ethical issues and practices on the advances of biosciences. It focuses on the need for balancing between moral demands of what ought to be in life and modern developments in the fields of biotechnology, biomedicine, environmental sciences and healthcare practices. It presents the justifications of acting morally, the place of ethics in the age of advancing science, the history, scope and approaches of bioethics. It also offers a comparative account of traditional theories of ethics, and briefly highlights ethical teachings of major religious traditions, with certain details about the scope and principles of the Islamic ethics. e book uses descriptive and comparative approaches and presents bioethical debates on genetically modified food, tissue engineering, environmental ethics, concerns of sharing body parties of organs and tissues, contraception and the moral predicaments of preventing the initiation of life, prolife and prochoice moral debates on abortion, infertility treatment and the ethics of parenthood, as well as the sanctity of life in the face of clinical trials.